DYNAMICS OF TRANSITION OF ABILITIES IN GENIUS: PSYCHOLOGICAL ASPECT OF ANALYSIS - Ралько, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the problem of development talent, skill and personality's significance for disclosure genius.